PENGARUH VARIASI LATIHAN TERHADAP SHOOTING PADA PERMAINAN SEPAKBOLA DI KLUB MENSUNGAI UNITED KABUPATEN SAMBAS - Taufik Hidayat; Ahmad Atiq; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The lack of ability of football players in mastering shooting techniques, makes theshooting carried out inaccurately towards the goal. Players focus more on kickingspeed so they can shoot quickly without paying attention to foot movements whenkicking the ball into the goal. It is necessary to do special exercises, for example byapplying a variety of exercises to increase the accuracy of players in shooting. Thepurpose of this study was to examine the effect of training variations on shooting atgoal in a soccer game. The research method used is quantitative with primary datatypes. The population in this study is the Mensungai United Football Club, SambasRegency. The collection of samples using total sampling technique and obtained asample of 18 players. Based on the research conducted, the results showed that theaverage value of the pretest was 10 while the average value of the posttest was14.3 with a difference in the average increase of 4.3 or 43%. T-test was used fordata analysis in this study. The calculation results from the T-test showed thatthere was a significant effect between the initial test and the final test. Thesignificance value obtained is 0.000 which is smaller than 0.05. As for the testscarried out, the results obtained that tcount (11,428)> ttable (2,109). From theseresults, it is known that Ha is accepted and H0 is rejected, which means thattraining variations affect shooting at goal in the football game at MensungaiUnited Club, Sambas Regency.Keywords: Variation, Practice, Shooting